2022
DOI: 10.1002/ieam.4704
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the optimum number of sample points to classify land cover types and estimate the contribution of trees on ecosystem services using the I‐Tree Canopy tool

Abstract: The process of producing information about dynamic land use and land cover and ecosystem health quickly with high accuracy and low cost is important. This information is one of the basic data used for sustainable land management. For this purpose, remote sensing technologies are generally used, and sampling points are mostly assigned. Determination of the optimum number of sampling points using the I-Tree Canopy tool was the main focus of this study. The I-Tree Canopy tool classifies land cover, revealing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Users can reveal the removal of pollutants causing air pollution from the atmosphere by trees according to the types of land cover they have determined, as well as the effects on ecosystem services for the capture and storage of atmospheric carbon with numerical data. Besides, the module is designed to provide easy and accurate estimation of monetary values (Hirabayashi, 2014;Selim et al, 2023). i-Tree recommends 500-1000 search points for studies, but reports that the more points identified, the better the prediction results will be (USDA, 2022).…”
Section: I-tree Canopy Toolmentioning
confidence: 99%
“…Users can reveal the removal of pollutants causing air pollution from the atmosphere by trees according to the types of land cover they have determined, as well as the effects on ecosystem services for the capture and storage of atmospheric carbon with numerical data. Besides, the module is designed to provide easy and accurate estimation of monetary values (Hirabayashi, 2014;Selim et al, 2023). i-Tree recommends 500-1000 search points for studies, but reports that the more points identified, the better the prediction results will be (USDA, 2022).…”
Section: I-tree Canopy Toolmentioning
confidence: 99%